Intangible assets and rights to them, constituting the formation of the authorized capital of enterprises, the basis of the marketing system - Olijnyk, H.; Bielova А. (Ways to Improve Construction Efficiency, 2020)
The world is now on the verge of large-scale transformations. This is happening under the influence of new digital technologies: multidimensional changes are taking place both at the global level and at the level of our state, industries, corporations. Companies change both externally and internally. External transformation introduces a new concept for working with clients, partners and contractors. At this stage, it is not enough to meet the client’s expectations, they must be able to foresee his requirements, that are growing every day. A significant number of surveys of top managers of companies around the world show that time-to-market for a product or service is days, not months or years, as it used to be, and this is one of the most difficult challenges of our time. The article examines the system of intangible asset management as part of a system of measures to increase the authorized capital of companies. Accounting, the formation of property rights to intangible assets and their contribution to the authorized capital of the company increases it by 70-80 percent, which should be a consequence for the formation of a new concept of enterprise management. The new concept will not work on the existing management and operational models, since in order to work in the digital world, companies must completely rebuild themselves from the middle and it is necessary to start with a clear formation of the authorized capital, which was not paid attention to during corporatization, since at that time there was a task of rapid transformations without preparation. This is how the joint-stock companies Ukrtelecom, Ukrposhta, and Ukrzaliznytsia were created. For these companies and especially for Ukrtelecom, as for a company in which there is no state property, it is time to develop methodological support, teach specialists and carry out a qualified inventory of all balance sheet items and form its authorized capital, taking into account the requirements of the digitalization of the system and the inclusion of intangible assets and property rights to them in the authorized capital. This is necessary because the traditional model of building a business in our state, the management system and the operating model of the company, are mainly static, focused on slow gradual development.